2012
DOI: 10.3329/dujps.v11i1.12483
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Extract of Syzygium cumini Shows Anti-Vibrio Activity Involving DNA Damage

Abstract: ABSTRACT:The aim of the study was to investigate the effect of an ethanol extract of leaf (EEL) of Syzygium cumini against Vibrio cholerae serogroups Ogawa and Inaba. The antimicrobial activity of EEL was evaluated by the disc diffusion method against multi-drug resistant Ogawa and Inaba. The EEL effectively inhibited the growth of both serogroups. This growth inhibition was accompanied by fragmentation of genomic DNA as revealed by agarose gel electrophoresis. This result suggested that the EEL might inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Pathogenic bacteria like E. coli, S. aureus and K. pneumonia on treatment with Caesalpinia coriaria glycosides and flavonoids for 24 h showed a smear of fragmented DNA (Anandhi et al 2014 ). Similarly the ethanolic leaf extract of S. cumini after treating V. cholerae showed fragmented DNA after 3 h of treatment (Ahsan et al 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…Pathogenic bacteria like E. coli, S. aureus and K. pneumonia on treatment with Caesalpinia coriaria glycosides and flavonoids for 24 h showed a smear of fragmented DNA (Anandhi et al 2014 ). Similarly the ethanolic leaf extract of S. cumini after treating V. cholerae showed fragmented DNA after 3 h of treatment (Ahsan et al 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…50 The ethanol extract of Jamun leaf has been reported to be active against the Vibrio cholerae serogroups Ogawa and Inaba. 51 The 70% ethanol extract of Jamun leaf, bark, pulp and seed showed a potent antimicrobial activity against various Gram-positive bacteria (including B. subtilis, B. cereus and S. aureus) and Gram-negative bacteria (including S. flexneri, P. aeruginosa and V. cholera). Comparison analysis showed that the leaf and bark extracts were more potent than the pulp and seed extracts.…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…Gel was observed under UV light and photographs were taken using gel documentation system. This test was done to observe whether the extract could cause fragmentation and degradation of Leptospira genomic DNA (Ahsan et al, 2012).…”
Section: Genomic Dna Damagementioning
confidence: 99%
“…There are many plant extracts that have shown to cause cell death involving bacterial DNA fragmentation. For example, the ethanol extract of Syzygium cumini leave has caused fragmentation of genomic DNA of Vibrio cholerae (Ahsan et al, 2012). Methanol and aqueous extracts from Eclipta alba and Phyllanthus amarus also resulted in fragmentation of the genome DNA of Leptospira sp.…”
Section: Genomic Dna Damagementioning
confidence: 99%